Involving Problem Based Learning as an Alternative for EFL Students Writing Improvement: A Method for Teaching Writing - Setlight, Kharisma C. M. S.; Betaubun, Martha; Kartika, Vicha (Journal of English Culture, Language, Literature and Education, 2023)
In fact writing is one of the language skills that is emphasized in learning English in Curriculum 2013 As one of the language skills writing skills need to be improved because it is a productive and expressive language skill that is needed to fulfill daily communication needs Seeing the crucial role of writing this present study intent to examine the problem based learning as an alternative model for EFL students writing improvement Classroom action research with two cycles was implemented to study this phenomena Moreover this study involved 18 students of class XI SMA YPPK YOS SUDARSO Merauke in collecting the data this study used observation sheet for both teacher and students activities meanwhile to see students writing improvement explanation text writing was applied in both cycles As the result Problem based learning could improve students writing it could be seen in each cycles scores where cycle I writing was 63 33 and improved in cycle II 81 In cycle I most of students did not pass the minimum completeness which was 75 meanwhile in cycle II most of students passed The improvement based on the observation results in both cycles are also being the success category in this study in cycle I both teacher and students obtained 67 85 good category and 57 14 enough category improved in cycle II which was 87 5 excellent category and 83 92 excellent category < p>